Invasive Haemophilus influenzae type a infection and polyarthritis in a 72-year-old Japanese man: A case report. Issue 7 (July 2021) - Kenzaka, Tsuneaki; Goda, Ken; Kubota, Mayumi; Takayanagi, Kosuke; Kenri, Tsuyoshi; Shibayama, Keigo; Akita, Hozuka
Abstract: Haemophilus influenzae is a small, nonmotile, non-spore-forming bacterium classified into 6 serotypes (a to f) and non-typeable strains that lack a capsule. Although H. influenzae serotype a (Hia) is prevalent in Canada, the United States, Brazil, Australia, across the African continent, and several other locations, it has not been reported in Japan thus far. Our case was of a 72-year-old Japanese man who sought medical consultation after presenting with chills, fever, and polyarthritis. Cultures of blood and synovial fluid from the left knee revealed H. influenzae infection. Diagnostic imaging showed poor contrast regions in both kidneys, fluid retention around both knee joints, the left shoulder joint, and both elbow joints. Subsequently, the patient was diagnosed with invasive H. influenzae infection accompanied by polyarthritis and renal infarction. 16S ribosomal RNA gene sequencing revealed that the bacterial strain was Hia. The patient was treated with antimicrobial agents and arthroscopic curettage. We present a case of invasive Hia infection accompanied by polyarthritis and renal infarction. To the best of our knowledge, this is the first case of Hia infection in Japan. The case is very rare considering that the disease occurred in an elderly patient who developed polyarthritis.